Augmented Reality in Education: A Primer - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal on Integrated Education, 2023)
Augmented reality is a significant emerging trend that is digitally enhancing our world. It superimposes sounds, videos, and graphics onto an existing environment. It is an interactive experience that brings digital content to the real world. The AR technology is useful in numerous fields including education because it enables an interactive experience with the real world. Augmented reality offers various benefits in education. It is gradually becoming the future of education. This paper provides various applications of AR technology in education.